Lightning search algorithm for optimal economic and emission dispatch of photovoltaic integrated with thermal power system - Nasser Nassar, Murad Yahya (2021)
Power dispatch plays an essential role in the planning process and control of modern power systems. Therefore, the optimization of the power dispatch problem is fundamental in the power system in order to achieve the optimal power output for minimizing generation cost and emission while satisfying operational system constraints. Many types of research have solved the power dispatch problem based on thermal power generation. However, it became more complex when integrating renewable energy (RE) such as photovoltaic (PV) in the system. Thus, both cost and emission level must be minimized to operate the power system economically and environmentally friendly. Solving this problem requires a good, fast, and robust algorithm. Therefore, this research proposed a lightning search algorithm (LSA) to solve the power dispatch problem for thermal and PV power generation for cost and emission minimization. The results obtained by LSA have been compared with other methods reported in the literature review. The LSA algorithm has been applied to determine the optimal power dispatch in six different conditions in this research. The first three conditions are minimizing economic dispatch (ED), emission dispatch (EmD), and combined economic and emission dispatch (CEED) on thermal power generation. Furthermore, the other three conditions are minimizing the ED, EmD, and CEED on thermal generation integrated with PV plants. The power balance and generator limits constraints have been considered in all test systems in this research. There are four-test systems, including 3, 6, 13, and 40 thermal units, to minimize operating costs. One test system consists of 6 thermal units that optimize EED and CEED problems on thermal generation. Then, the test system consists of 6 thermal incorporated with thirteen PV units to minimize EED and CEED problems for 24 hours. It can be concluded that LSA was able to solve the power dispatch rightly whether it used to optimize the multi-objective or single objective. Furthermore, it is found that the LSA technique outperformed the compared algorithms that existed in the literature of this research in obtaining better solution quality.